2020
DOI: 10.4187/respcare.08038
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Environmental Smoke Exposure During Pediatric Hospitalization: Attitudes and Practices of Pediatric Nurses Versus Respiratory Therapists

Abstract: BACKGROUND: Tobacco smoke exposure leads to numerous adverse health effects in children. Providing cessation interventions to caregivers who smoke during pediatric hospitalizations can help protect children from such exposure. Both pediatric registered nurses (RNs) and pediatric respiratory therapists (RTs) are well positioned to provide these interventions. Little is known about their rates of participation in cessation efforts. Our objective was to compare the attitudes and practice of pediatric RNs versus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
3
2
0
Order By: Relevance
“…Of 902 parents whose child was reviewed by a paediatrician or general practitioner in the study, only 50% had been asked about their smoking status by the health professional. Similar results were found in a study conducted by Williams et al 14 focusing on nurses, and found that only 18.8% of registered nurses ‘often’ or ‘always’ identified the smoking status of parents of hospitalised children and only 13.4% would offer quit support/education. Major barriers reported included confidence in knowledge and skills to provide this support, parents being resistant to discussing smoking and short hospital stays 14 .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Of 902 parents whose child was reviewed by a paediatrician or general practitioner in the study, only 50% had been asked about their smoking status by the health professional. Similar results were found in a study conducted by Williams et al 14 focusing on nurses, and found that only 18.8% of registered nurses ‘often’ or ‘always’ identified the smoking status of parents of hospitalised children and only 13.4% would offer quit support/education. Major barriers reported included confidence in knowledge and skills to provide this support, parents being resistant to discussing smoking and short hospital stays 14 .…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were found in a study conducted by Williams et al 14 focusing on nurses, and found that only 18.8% of registered nurses ‘often’ or ‘always’ identified the smoking status of parents of hospitalised children and only 13.4% would offer quit support/education. Major barriers reported included confidence in knowledge and skills to provide this support, parents being resistant to discussing smoking and short hospital stays 14 . Our study produced similar results with only 27% of paediatric hospital nursing departments identifying the smoking status of parents or carers as standard practice.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…There have been substantial efforts to make evidencebased tobacco dependence treatments available through the healthcare delivery system (Baker et al, 2021;Cook et al, 2021;Fiore et al, 2021;Fiore et al, 2008;Hurt et al, 2009;Ramsey et al, 2020;Sarna et al, 2020;Trapskin et al, in press;Williams et al, 2021). Unfortunately, these efforts have not typically extended to behavioral health care systems that uncommonly provide cessation treatment programs.…”
Section: Introductionmentioning
confidence: 99%